Optimisasi Field of View (FOV) Terhadap Kualitas Citra Pada T2WI FSE MRI Lumbal Sagital - Fatimah Fatimah; Johannes Dahjono; Metria Riza Sativa (Poltekkes Kemenkes Semarang, 2015)
Background : Field of view (FOV) is one of paramaters in MRI that is possibly adjusted by a radiographer. Many various adjusment of FOV that are using for lumbar MR Imaging. This study is to determine the effect of variations in the value of FOV to the image quality and anatomical information.Methods : This is a quasy experimental research. The study was conducted with 1.5 Tesla MRI. Data were collected from three volunteers with 5 variations of FOV (17cm, 22cm, 27cm, 32cm and 37cm) which is totally 15 images acquired. Images were evaluated according to the objective evaluation of SNR and CNR by a software in the MRI machine. Quntitative measurements of SNR were conducted on corpus vertebrae, discus intervertebralis, medulla spinalis, cerebrospinal fluid (CSF) and ligamentum flavum respectively. While CNR measurements were on CSF-corpus vertebra, CSF-discus intervertebralis, CSF-medulla spinalis, medulla spinalis-corpus vertebra, medulla spinalis-discus intervertebralis and corpus vertebra-discus intervertebralis. For conspicuity, overall image contrast and artifacts were evaluated qualitatively by three radiologists scoring on the paper sheet based on the image of corpus vertebrae, discus intervertebralis, medulla spinalis, cerebrospinal fluid, ligamentum flavum. Quantitative data of SNR and CNR value were analyzed using Linier Regression and Correlation Spearman test. While radiologists scoring were analyzed using Friedman test and cross tabulation.Results : The results showed that FOV variations affect the image qualities of T2WI FSE sagital lumbar MR Imaging. FOV variations are significantly corelate to the SNR of corpus vertebra, discus intervertebralis, medulla spinalis, CSF and ligamentum flavum. FOV variations are also significantly correlate to the CNR value of CSF-corpus vertebra, CSF-discus intervertebralis, CSF-medulla spinalis, medulla spinalis-corpus vertebra and medulla spinalis-discus intervertebralis (p values 0,05) with positive correlation. But there is no correlation between FOV variations and CNR at the corpus vertebra-discus intervertebralis (p values = 0,109).Conclusion : Based on these results indicate that overall image and artifacts are relatively similar for all value of FOV variations. Optimal values of FOV for T2WI FSE sagittal lumbar MR Imaging is a FOV of 27 cm.